2016
DOI: 10.1007/s11356-016-6697-y
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric deposition of organochlorine pesticides by precipitation in a coastal area

Abstract: Wet deposition fluxes of organochlorine pesticides (OCPs) were determined for rain samples collected in a coastal area of Turkey. Seventeen precipitation samples were collected over a 1-year period from 2008 to 2009. Rainwater was accumulated at the beginning of rain events using real time monitoring. Atmospheric concentrations were also measured in parallel with deposition samples. Both atmospheric concentrations and deposition fluxes were determined as particle and gas phases. The particle phase and dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In comparing international treatment processes for harvested rainwater, it should be kept in mind that differences in local standards would affect the proposed treatment processes. In most investigations, inorganic compounds were measured, but Cindoruk and Ozturk [51] showed that organochlorine pesticides can be found in rainwater in several places in the world, and the presence of polycyclic hydrocarbons was demonstrated by Göbel et al [52] and Angrill, Petit-Boix, Morales-Pinzón, Josa, Rieradevall and Gabarrell [18]. An overview of the concentrations generally found in rainwater is shown in the Supplementary Information Tables S3-S8. Problems with water quality mainly arise from contamination during the collection of water, when the rainwater is in contact with hard surfaces.…”
Section: Rainwater Qualitymentioning
confidence: 99%
“…In comparing international treatment processes for harvested rainwater, it should be kept in mind that differences in local standards would affect the proposed treatment processes. In most investigations, inorganic compounds were measured, but Cindoruk and Ozturk [51] showed that organochlorine pesticides can be found in rainwater in several places in the world, and the presence of polycyclic hydrocarbons was demonstrated by Göbel et al [52] and Angrill, Petit-Boix, Morales-Pinzón, Josa, Rieradevall and Gabarrell [18]. An overview of the concentrations generally found in rainwater is shown in the Supplementary Information Tables S3-S8. Problems with water quality mainly arise from contamination during the collection of water, when the rainwater is in contact with hard surfaces.…”
Section: Rainwater Qualitymentioning
confidence: 99%
“…these compounds are redistributed (tiryaki & temur 2010) into different environmental compartments (i.e. air, water, and soil) via wind dispersion, as well as via wet (Cindoruk & ozturk 2016) and dry deposition (Sauret et al 2009). Some pesticides and degradation products may remain in the environment long after application.…”
Section: Introductionmentioning
confidence: 99%